Pengaruh Variasi Media Terhadap Motivasi Belajar Ips Siswa Kelas Viii Sekolah Menengah Pertama Negeri 4 Tambang Kabupaten Kampar - Jauza Salsabila; Aramudin . (CV. ITTC INDONESIA, 2026)
This research aimed at finding out the effect of media variation toward student Social Science learning motivation at the eighth grade of State Junior High School 4 Tambang, Kampar Regency. This research was instigated with the low of student learning motivation, including the lack of media utilization, a less conducive environment, and the lack of appreciation in learning. It was quantitative research with quasi experimental research type (nonequivalent control group design). The eighth-grade students were the population of this research, and they were 305 students. The research samples were the eighth-grade students of classes 4 (control group) and 5 (experimental group), and they were 60 students. Questionnaire, observation, and documentation were the techniques of collecting data. Based on the research findings and data analyses, there was a significant effect of media variation toward student Social Science learning motivation at the eighth grade of State Junior High School 4 Tambang, Kampar Regency, it could be identified from the score 2.72, it was modest effect (simple effect), and the effect size test stated that there was an effect of media variation toward student learning motivation. T-test showed that t table with df 58 and 5% significant level was 1.701. The score of significance was 0.000 lower than 0.05, and there was a significant difference so that the calculation result of observed was higher than t table, or 11.339>1.701. It meant that H0 was rejected, and Ha was accepted. It could be concluded that there was a significant effect of media variation toward student Social Science learning motivation.